Nanorremediação em diferentes solos contaminados com Pentaclorofenol (PCP) - Manfron, Sidiane (2020)
The Pentachlorophenol (PCP) is an organochlorine compound capable of contaminating the soil and the water. It is highly toxic and carcinogenic. Studies have shown the ability of zero valence iron nanoparticles (nFeZ) to act on the PCP, since they have the oxidation and reduction potential and act on the direct transfer of electrons between particles, generating dehalogenation and / or reductive dechlorination. The iron nanoparticles, because their high reactivity, mobility in porous media and low toxicity, are considered important decontamination agents, but they can act differently according to the physical-chemical characteristics of the soil. In this sense, the purpose of this research was to evaluate the efficiency of nFeZ for PCP degradation in different types of natural soils. Four different kinds of soil that belong to the four geological regions of the state of Rio Grande do Sul, Brasil, were analyzed. They cover the Oxisol from the State Northern Highlands, the Argisole from the Central Valley, the Planosols from the Rio-Grandense Shield e Gleysols from the Coastal Plain. We performed chemical, granulometric, diffraction and X-ray fluorescence analyses for the physical-chemical characterization of soils before contamination by PCP. The soils were contaminated with a standard solution of PCP solubilized with hexane (100 mg/L). The samples were divided and two concentrations of nFeZ were utilized – 25g/kg e 50g/kg, whose efficiency were analyzed on days 1, 7, 15 and 30. For the data analysis, the Kruskal-Wallis test was used to analyze the variables of time, concentration and soil in the PCP degradation effect (p<0,05). In the chemical-physical characterization of soils, it was observed that Oxisol and Argisol were classified as clayey, showing a low pH, high organic matter content and cation exchange capacity, with predominant clay formation 1:1 (kaolinite and hematite). The Planosol was classified as sandy loam clay and the Gleysol, as sandy loam, both with less acidity, little organic matter and low cation exchange capability, as well as with a predominance of clay minerals of 2:1 (albite and montmorillonite). Regarding the efficiency of nFeZ over PCP, the soil type variable did not shown statistically significant difference, that is, the chemical, physical and mineralogical differences of the soils had no influence on PCP degradation by nFeZ. The reactivity time and concentration differences of the iron nanoparticles were statistically meaningful for PCP degradation. The 50g/kg concentration had higher peak of degradation in the first 7 days, declining over time. In the 25g/kg concentration, the greatest degradation was observed in the Plansol, with and efficiency of 66,72%, followed by theGleysol (63,56%), Oxisol (58,60%) and Argisol (57,07%). In the 50g/kg concentration, the greatest degradation was in the Plansol (86,59%), followed by Gleysol (74,18%), Argisol (72,98%) e Oxisol (72,76%). The results obtained show that a higher incidence of colloids in the soil, as occurs in the clay soils, may create less reactive spaces for the action of nFeZ, as this nanoparticle is also absorbed on them. In sandy soils, there are larger spaces between their micro-structures, with the iron nanoparticles being more reactive and, consequently, having action against the PCP.